DETERMINAN GEJALA KEJADIAN DISMENORE PADA MAHASISWI UNIVERSITAS MUHAMMADIYAH PROF. DR. HAMKA JAKARTA - Nabila Hidayanti; Retno Mardhiati Adiwiryono (Jurnal Pendidikan Kesehatan, 2021)
Dysmenorrhea is experienced by the age of menarche or teenagers. However, there are still many adults such as students who experience dysmenorrhea. The research objective was to determine the determinants of dysmenorrhea symptoms in students of Prof. DR. HAMKA 2020. This research is quantitative research with cross sectional approach. Population of this study were undergraduate and D3 students of Prof. DR. HAMKA. The sampling technique used quota sampling technique with a total sample of 150 respondents. Univariate results showed symptoms of dysmenorrhea 135 or 90.0 percent, normal menarche age 147 or 98.0 percent, normal menstrual length 116 or 77.3 percent, abnormal menstrual cycle 105 or 70.0 percent, perceived rate of menstruation 120 or 80.0 percent, family history 116 or 77.3 percent, irregular exercise habits 128 or 85.3 percent, and stress 139 or 92.7 percent. The bivariate results showed that there was a relationship between family history and symptoms of dysmenorrhea or p value 0.003, there was a relationship between the menstrual cycle and symptoms of dysmenorrhea or p value 0.038, and there was a relationship between perceptions of menstrual rate and symptoms of dysmenorrhea or p value 0.041. Based on the results of the research, it is suggested that faculties outside the health faculty can also provide health related materials for their students to be better prepared to maintain health.